The genetic basis and cell of origin of mixed phenotype acute leukaemia. (18th October 2018) - Alexander, Thomas; Gu, Zhaohui; Iacobucci, Ilaria; Dickerson, Kirsten; Choi, John; Xu, Beisi; Payne-Turner, Debbie; Yoshihara, Hiroki; Loh, Mignon; Horan, John; Buldini, Barbara; Basso, Giuseppe; et al.
Abstract Mixed phenotype acute leukaemia (MPAL) is a high-risk subtype of leukaemia with myeloid and lymphoid features, limited genetic characterization, and a lack of consensus regarding appropriate therapy. Here we show that the two principal subtypes of MPAL, T/myeloid (T/M) and B/myeloid (B/M), are genetically distinct. Rearrangement ofZNF384 is common in B/M MPAL, and biallelicWT1 alterations are common in T/M MPAL, which shares genomic features with early T-cell precursor acute lymphoblastic leukaemia. We show that the intratumoral immunophenotypic heterogeneity characteristic of MPAL is independent of somatic genetic variation, that founding lesions arise in primitive haematopoietic progenitors, and that individual phenotypic subpopulations can reconstitute the immunophenotypic diversity in vivo. These findings indicate that the cell of origin and founding lesions, rather than an accumulation of distinct genomic alterations, prime tumour cells for lineage promiscuity. Moreover, these findings position MPAL in the spectrum of immature leukaemias and provide a genetically informed framework for future clinical trials of potential treatments for MPAL. A large-scale genomics study shows that the cell of origin and founding mutations determine disease subtype and lead to the expression of multiple haematopoietic lineage-defining antigens in mixed phenotype acute leukaemia.